Normal blood flow velocities of basal cerebral arteries decrease with advancing age: A Transcranial Doppler sonography study - ULUÇ, KAYIHAN (TOHOKU UNIV MEDICAL PRESS, 2008)
Transcramal Doppler sonography (TCD) is a non-invasive diagnostic tool enabling evaluation of blood flow characteristics of basal intracerebral vessels via thin calvarian regions. Several factors may affect the normal values of cerebral hemodynamic parameters, and standard reference values for each laboratory are needed for precise interpretation of the results. The aims of this study were to determine normal values of flow velocities of basal cerebral arteries of our TCD laboratory, and to study the influence of age and gender on normal values. We studied 63 healthy volunteers (30 male and 33 females; age range, 5 69 years old) with TCD with a 2-MHz transcranial probe. The subjects were divided into 7 age groups: 5-10 years, 11-20 years, 21-30 years, 31-40 years, 41-50 years, 51-60 years and > 60 years. Mean velocity (V mean), peak systolic velocity (PSV), and end-diastolic velocities (EDV) were determined in middle, anterior and posterior cerebral arteries. No significant gender difference was found. However, there was a decrease in blood flow velocities in all vessels with advancing age, which was significant when subjects older than 40 years and <= 40 years old were compared. V mean, PSV and EDV values were highest in the age group of 5-10 years old and lowest in volunteers older than the age of 60 (p < 0.05). As a conclusion, flow velocities in basal cerebral arteries range widely and are significantly age-related. Age matching of TCD data is a requirement for clinically relevant conclusions.
Keywords: Transcranial Doppler sonography; basal; cerebral arteries; normal values; healthy subjects; REFERENCE VALUES; ULTRASOUND